Giant cell arteritis and cardiovascular disease in older adults - Ray, J G (Copyright 2005 by Heart, 2005)
Objective: To explore the association between giant cell arteritis (GCA) and subsequent cardiovascular disease in older adults. Design: Population based retrospective cohort study. Setting: The entire province of Ontario, Canada. Participants: Patients aged 66 years and older with newly diagnosed GCA (n = 1141), osteoarthritis (n = 172 953), or neither (n = 200 000). Patients with neither were randomly selected from the general population and formed the control group. Main outcome measures: The primary composite outcome was based on a subsequent diagnosis or surgical treatment for coronary artery disease, stroke, peripheral arterial disease, or aneurysm or dissection of the aorta. Results: The composite end point was more common in seniors with GCA (12.1/1000 person-years) than in patients with osteoarthritis (7.3/1000 person-years) or neither condition (5.3/1000 person-years). The adjusted hazard ratio for cardiovascular disease was 1.6 (95% confidence interval (CI) 1.1 to 2.2) in patients with GCA versus patients with osteoarthritis, and 2.1 (95% CI 1.5 to 3.0) in patients with GCA versus unaffected controls. Conclusions: Older adults with GCA appear to be at increased risk for developing cardiovascular disease. Whether an aggressive approach to cardiovascular risk factor modification is particularly beneficial in these patients remains to be determined.